The Influence of Board of Directors, Board of Commissioners, and Independent Commissioners on Company Financial Performance - Islam, Alifia Izzah (Universitas Hamzanwadi, 2024)
Assessing a company's financial performance is crucial, as it serves as a benchmark for potential investors when considering investment in the company's stocks. This research sought to examine the impact of the board of directors, board of commissioners, and independent commissioners on a firm's financial performance, evaluated using financial ratios. The study concentrated on pharmaceutical companies registered on the Indonesia Stock Exchange (IDX) during the period from 2018 to 2022. The results indicate that while the size of the board of directors does not exert a significant influence, both the board of commissioners and independent commissioners contribute to shaping the financial performance of the company